2017
DOI: 10.1186/s40662-017-0088-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carotenoids dietary supplementation on macular function in diabetic patients

Abstract: BackgroundDiabetic retinopathy is a major cause of visual impairment and blindness among working-age people worldwide. The aim of our study was to investigate the effects of a carotenoid supplementation on retinal thickness and macular function of patients with diabetes using optical coherence tomography (OCT) and multifocal electroretinography (mfERG).MethodsA retrospective study of one hundred and twenty eyes of sixty patients age between 40 and 60 years with non-insulin dependent type 2 diabetes mellitus wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
1
41
0
1
Order By: Relevance
“…In the diabetic mouse, lutein treatment effectively prevents retinal changes [ 75 ]. Moreover, lutein supplementation is associated with improved visual function in patients with NPDR [ 71 ] ( Table 4 ).…”
Section: Current and Novel Treatment Strategies In Drmentioning
confidence: 99%
“…In the diabetic mouse, lutein treatment effectively prevents retinal changes [ 75 ]. Moreover, lutein supplementation is associated with improved visual function in patients with NPDR [ 71 ] ( Table 4 ).…”
Section: Current and Novel Treatment Strategies In Drmentioning
confidence: 99%
“…The results of the present study revealed that lutein (10 mg/day)-, zeaxanthin (2 mg/day)-, and mesozeaxanthin (10 mg/day)-containing supplement improved retinal histological change and visual function. 30 Sahli et al revealed that consumption of high lutein and zeaxanthin food was not associated with a decrease in DR incidence in a six-year prospective cohort study. 31 Zhang et al study the impacts of lutein on diabetic patients with DR in a placebo-controlled clinical trial.…”
Section: Studies Evaluating the Effects Of Carotenoids On Dr In Humansmentioning
confidence: 99%
“…This study was consistent with the results conclude from supplementation of 10 mg/day lutein for 36 weeks in patients with nonproliferative DR [83]. A recent study has shown an increased thickness in the central fovea and improved retinal response density after 2-year supplementation of combined lutein (10 mg/day), zeaxanthin (2 mg/day), and mesozeaxanthin (10 mg/day) in type 2 diabetic patients without DR, indicating beneficial effects of xanthophylls on visual functions in diabetes [84].…”
Section: Clinical Trialsmentioning
confidence: 99%